Decomposition of Differences between Household Income Distributions in Poland in Years 2002 and 2012 - Landmesser, Joanna Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
In this study we present the decomposition of income inequalities between household income distributions in Poland in 2002 and 2012. The difference between two distributions may be decomposed using the counterfactual distribution, which can be constructed in various ways. Techniques such as the residual imputation approach and RIF‑regression method (recentered influence function) were considered. The application of these methods made it possible to show the aggregate detailed decompositions in different quantile points along the income distribution. The influence of several person’s characteristics on the differences in income distributions was examined. By decomposing the inequalities into the explained and unexplained components it was possible to receive additional information about their causes.